Integration of Artificial Intelligence in the Learning Process: Its Impact on Students' Learning Independence and Critical Thinking - Mufid Mufid (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study examines the integration of artificial intelligence (AI) into the learning process and its impact on students' independent learning and critical thinking skills through a qualitative literature review approach. The study identifies that the use of AI in education offers significant opportunities for personalized learning, adaptive feedback, and support for the development of students' cognitive skills aligned with the demands of 21st-century skills. The literature shows that AI encourages students to manage their learning process more autonomously, but on the other hand, excessive reliance on AI systems can hinder independent initiative and reflective reasoning processes. The study also found that the use of AI features needs to be combined with pedagogical strategies that encourage active student engagement to maximize critical thinking skills. Recent literature findings underscore the importance of educators' role in guiding and guiding the use of technology so that AI integration not only facilitates content access but also strengthens the development of higher-level cognitive competencies. The study's conclusions confirm that AI integration can enrich students' learning experiences when implemented consciously, purposefully, and based on a strong learning design and relevant pedagogical framework.